Copula-based joint probability model for multi-peak wave slamming forces on box girder bridges - Lixuan Fei; Qinghe Fang; Pengfei Liu; Guochen Zhao; Anxin Guo (Engineering Structures, 2026)

Longitudinal soil arch evolution in cobble tunnels using shallow tunnelling method: Experimental and DEM insights - Yiwen Qin; Fengyin Liu; Jinxing Lai; Junling Qiu; Guochen Tang; Wencai Zhao (Tunnelling and Underground Space Technology, 2026)

In situ halide-mediated engineering enabling cascaded alloying-conversion reactions in Ag/Fe3O4/C composite for high-performance potassium-ion batteries - Ji Ma; Jian Zhang; Shen Zhang; Mingyan Zheng; Suqing Feng; Jianglong Ping; Yujie Zhang; Kunpeng Huang; Guochen Pu; Hang Tian; Wenhao Sheng; Yichuan Zhang; et al. (Chemical Engineering Journal, 2026)

Ship emissions amplify soluble iron in PM2.5 in a typical coastal port in North China - Yiqi Chen; Wei Tan; Yuan Fang; Qi Yuan; Yujue Wang; Weiwei Guan; Minkang Zhi; Xiaohuan Liu; Liang Xu; Jian Zhang; Guochen Wang; Xiaohong Yao; et al. (Environmental Pollution, 2026)

Wollastonite enhances microbial diversity and ecological network stability - Yanzhi Wang; Yongfeng Wang; Ronghua Kang; Chunjie Tian; Guochen Li; Feifei Zhu; Ang Wang; Geshere Abdisa Gurmesa; Chenxia Su; Chang Liu; Dong Liu; Zhi Quan; et al. (Applied Soil Ecology, 2026)

Data-Driven Insights and Prediction of Bauxite-Hosted Lithium Mineralization - Xiaokang Liang; Guotao Sun; Yong Fu; Bo Tang; Peiwen Chen; Zaiping Shi; Shijiang Yang; Guochen Zhou; Zhonghong Huang; Qiaolin Fu; Tianyi Liu (Natural Resources Research, 2026)

Constructed wetland substrate–mediated stereoselective transformation of metolachlor: Influence of redox conditions and microbial community dynamics - Liangjin Chen; Yucong Zheng; Mawuli Dzakpasu; Qian Yang; Guochen Liu; Liping Zhao; Tianfu Wu; Dongfu Zhang; Xiaochang Wang; Rong Chen (Environmental Research, 2026)

Molecular engineering for synthesizing flocculation /extraction bifunctional polymer and one-way liquid–liquid mass transfer at oil/water interfaces - Guo Liu; Xing Luo; Shengxin Wang; Yulin Shi; Guochen Bai; Heling Guo; Ayyaz Ahmad; Tingting Wei (Desalination, 2026)

Molecular phylogeography and population history of Saccostrea mordax based on mitochondrial DNA - Zeyu Tang; Cui Li; Guochen Zang; Zhenqiang Liu; Zongmei Cui; Haiyan Wang (Journal of Oceanology and Limnology, 2026)

Neoarchean crustal thickness and geothermal gradient of northwestern Yangtze Craton, South China: Constraints from geochemistry and zircon U-Pb-Hf isotopes of TTGs - Peiwen Liu; Xiaozhong Ding; Yanxue Liu; Guochen Dong; Jibiao Zhang; Tingdong Li (Lithos, 2025)

Wollastonite improves soybean yield without toxic trace elements enrichment - Yanzhi Wang; Ji Chen; Guochen Li; Chao Gong; Ang Wang; Ronghua Kang; Feifei Zhu; Jiaoyue Wang; Chang Liu; Dong Liu; Chenxia Su; Quanping Zhang; et al. (Nutrient Cycling in Agroecosystems, 2025)

MoO3-MoS2 with abundant oxygen vacancies for real-time seafood quality assessment - Guochen Qi; Shuwei Ren; Jingfang Ji; Hao Gao; Zhichuang Ma; Sufeng Fan; Pan Liu; Jingmin Ge (Chemical Engineering Journal, 2025)

Organic nitrates in coastal aerosols: Seasonal dynamics, influencing factors, and formation pathways - Mengke Tian; Zhijian Ding; Jia Chen; Juntao Huo; Guochen Wang; Jian Xu; Hao Li; Ziwei Liu; Yunkai Wang; Nan Ye; Xiaofei Qin; Yanfen Lin; et al. (Atmospheric Environment, 2025)

Design and testing of the clam vibration harvester's V-shaped double-spiral harvesting roller brush based on DEM-MBD - Li Hangqi; Mu Gang; Li Xiuchen; Wu Hao; Xu Bin; Liu Fawei; Sun Zhenyin; Zhang Qian; Zhang Hanbing; Xin Mingjin; Zhang Guochen (Aquacultural Engineering, 2025)

Mechanical Characterization and Dual-Layer Discrete Element Modeling of Mactra veneriformis - Bin Xu; Yazhou Yang; Hangqi Li; Guangcong Chen; Yizhi Chang; Feihong Guo; Hao Wu; Jixuan Zhao; Zijing Liu; Guochen Zhang; Xiuchen Li; Hanbing Zhang; et al. (Fishes, 2025)
The discrete element model of Mactra veneriformis currently employs an oversimplified multi-sphere approach using EDEM’s Hertz–Mindlin model, assuming uniform shell–flesh mechanical properties. This study developed an advanced dual-layer flexible bonding model through comprehensive biomechanical testing. Mechanical properties and shell morphology were experimentally characterized to inform model development. Parameter optimization combined free-fall experiments with Plackett–Burman screening, steepest ascent method, and Box–Behnken RSM, yielding optimal contact parameters: flesh–flesh stiffness (X1) = 3.64 × 1011 N/m3, shell–flesh interface (X3) = 1.48×1013 N/m3, shell–shell tangential stiffness (X6) = 3.23 × 1012 N/m3, and normal strength (X7) = 8.35 × 106 Pa. Validation showed only 4.89% deviation between simulated and actual drop tests, with hydraulic impact tests confirming excellent model accuracy. The developed model accurately predicts mechanical behavior and shell fracture patterns during harvesting operations. This research provides a validated numerical tool for optimizing clam cultivation and harvesting equipment design, offering significant potential to reduce shell damage while improving harvesting efficiency in bivalve aquaculture systems.

The construction of flocculation-to-extraction coupled system with a novel dual-functional polymer for dye wastewater treatment and reuse - Guochen Bai; Guo Liu; Tingmin Ran; Yulin Shi (Environmental Research, 2025)

Smart UAV-assisted blueberry maturity monitoring with Mamba-based computer vision - Fan Zhao; Yinyin He; Jian Song; Jiaqi Wang; Dianhan Xi; Xinlei Shao; Qingyang Wu; Yongying Liu; Yijia Chen; Guochen Zhang; Chenyu Zhang; Yulun Chen; et al. (Precision Agriculture, 2025)
Purpose Precise segmentation of blueberry maturity is critical for optimizing harvestschedules and maintaining product quality. Traditional methods, which rely on manualinspection, are not only labor-intensive but also cost-inefficient. This study presents a novelframework that integrates deep learning-based super-resolution reconstruction (SRR) withsemantic segmentation to provide a fast and accurate solution for maturity assessment. Methods The SRR module enhances image resolution, enabling more detailed feature extraction.Semantic segmentation models—incorporating convolutional neural networks (CNNs),Transformer-based models, and the Mamba-based state space architecture—further improvesegmentation precision. Results Experimental results indicate that the MambaIR modelachieves a structural similarity index measure (SSIM) of 82.26% in SRR tasks, while the Mamba-based segmentation model attains a mean Intersection over Union (mIoU) of 83.15%. Conclusion By uniting SRR and semantic segmentation, our framework not only advances thetechnical accuracy of maturity detection but also holds strong potential for real-time, cost-effective deployment in precision agriculture systems, supporting intelligent decision-making at scale.

Seafloor debris detection using underwater images and deep learning-driven image restoration: A case study from Koh Tao, Thailand - Fan Zhao; Baoxi Huang; Jiaqi Wang; Xinlei Shao; Qingyang Wu; Dianhan Xi; Yongying Liu; Yijia Chen; Guochen Zhang; Zhiyan Ren; Jundong Chen; Katsunori Mizuno (Marine Pollution Bulletin, 2025)

Size-Selective Harvesting Effects on Reproductive Investment in Marine Medaka (Oryzias melastigma) - Guochen Gan; Guankui Liu; Xinyao Sun; Wenbo Deng; Fengming Lv; Yongjun Tian; Peng Sun (Fishes, 2025)
Long-term selective fishing pressure often leads to miniaturization, smaller size, and early sexual maturity in many commercial fish species. To adapt, these species increase energy allocations toward maturation and reproduction, which can reduce population productivity and recruitment. However, how different fishing pressures affect reproductive investment and energy allocation between growth and reproduction remains unclear. In this study, we designed three size-selective harvesting strategies—large, random, and small harvests—to examine their effects on the growth and reproductive investment of marine medaka (Oryzias melastigma). We analyzed changes in length, weight, and gonad weight across different harvest times. Results showed that the “large harvest” group allocated more energy to reproduction, leading to miniaturization and earlier maturation, while the “small harvest” group focused more on growth, resulting in larger fish at the same age. This study provides experimental evidence on how size-selective harvesting alters reproductive investment in fish populations, offering valuable insights for the sustainable exploitation of fishery resources.

Bioorthogonal click chemistry and aptamer-targeting enables highly selective fluorescence labeling of exosomal glycosylated EpCAM for super resolved imaging - Zichun Li; Yifan Liu; Feiran Liu; Guochen Sun; Xiaoling Zhang; Jing Jing (Analytica Chimica Acta, 2025)

Transient HR enhancement by RAD51-stimulatory compound confers protection on intestinal rather than hematopoietic tissue against irradiation in mice - Zhiyu Lu; Dong Chen; Ning Zhang; Zhiyuan Zheng; Zimo Zhou; Guochen Liu; Jiawei An; Yong Wang; Yongping Su; Wensheng Chen; Fengchao Wang (DNA Repair, 2024)

Multi-process atmospheric particle number size distribution over the Bohai Sea: Insights from cruise and onboard unmanned aerial vehicle observations - Ziwei Liu; Hao Li; Jie Tang; Mian Wang; Haitao Zheng; Tao Luo; Xiaoquan Song; Chengfeng Liu; Guochen Wang; Xiaofei Qin; Jia Chen; Da Lu; et al. (Atmospheric Environment, 2024)

Species composition and distribution of common Crassostrea and Saccostrea oysters along the coast of Hainan Island - Ruijing Lu; Ya Chen; Peizhen Ma; Cui Li; Zhen Zhang; Guochen Zang; Zhenqiang Liu; Haiyan Wang (Journal of Oceanology and Limnology, 2024)

Transpiration and water use sources of poplar (Populus × xiaozhuanica) plantations with 7-years vs. 20-years old in a semiarid sandy region of Northeast China - Lining Song; Jiaojun Zhu; Xin Liu; Jinxin Zhang; Xiao Zheng; Yirong Sun; Guochen Wang; Linyou Lü (Agricultural and Forest Meteorology, 2024)

Design and synthesis of low-potential and cycling-stable cobalt dicarboxylate bipyridine complexes for high-voltage aqueous organic redox flow batteries - Bin Liu; Wei Wei; Yu Wang; Manrong Song; Youke Chen; Honglin Chen; Liuping Chen; Qiuxia Dai; Shengxin Yao; Junhui Xu; Guochen Jia; Tianshou Zhao (Science Bulletin, 2024)

Wasserstein distance-based full waveform inversion method for density reconstruction - Hongying Liu; Guochen Wu; Zongfeng Jia; Qingyang Li; Junzhen Shan; Sen Yang (Journal of Applied Geophysics, 2024)

Wollastonite powder application increases rice yield and CO2 sequestration in a paddy field in Northeast China - Fangna Wang; Feifei Zhu; Deze Liu; Yuying Qu; Dong Liu; Jin Xie; Ang Wang; Ronghua Kang; Zhi Quan; Yinghua Li; Xin Chen; Guochen Li; et al. (Plant and Soil, 2024)

Unveiling the pollution and risk of atmospheric (gaseous and particulate) polycyclic aromatic hydrocarbons (PAHs) in a heavily polluted Chinese city: A multi-site observation research - Tao Wang; Luyao Zhang; Pei Zhang; Guangyuan Yu; Chong Chen; Xiaofei Qin; Guochen Wang; Xiansheng Liu; Rui Li; Liwu Zhang; Zhonghuan Xia (Journal of Cleaner Production, 2023)

Vitamin B ameliorates PM2.5-induced kidney damage by reducing endoplasmic reticulum stress and oxidative stress in pregnant mice and HK-2 - Chunming Xu; Qian Zhang; Guochen Huang; Jia Huang; Xiaoyan Fu; Meifang Liu; Yonghong Sun; Hongxia Zhang (Toxicology, 2023)

Relationship between light absorption properties of black carbon and aerosol origin at a background coastal site - Haiyan Li; Chengfeng Liu; Hao Li; Guochen Wang; Xiaofei Qin; Jia Chen; Yanfen Lin; Juntao Huo; Qingyan Fu; Yusen Duan; Congrui Deng; Kan Huang (Science of The Total Environment, 2023)

Emplacement and evolution of zoned plutons: Multiproxy isotopic and geochemical evidence from the peraluminous Laojunshan leucogranite suite, southwestern China, and implications on the regional geodynamic and metallogenic history - Yanbin Liu; Lifei Zhang; M. Santosh; Guochen Dong; Chaoyang Que; Chengxue Yang (Gondwana Research, 2023)

Design and testing of a mechanized brush-screen cooperative vibration harvester for mudflat-buried shellfish based on the discrete element method - Hangqi Li; Gang Mu; Hanbing Zhang; Hao Wu; Fawei Liu; Zhenyin Sun; Qian Zhang; Yizhou Wang; Yurui Wang; Xiuchen Li; Guochen Zhang (Frontiers in Marine Science, 2023)
Introduction To enhance the application of mechanized harvesting and supplement research on harvesting theory in mudflat-buried shellfish harvesting in China, a brush-screen cooperative mudflat-buried shellfish vibration harvester was designed. Methods The harvester is primarily composed of a crank rocker double-layer vibrating screen, two stage rolling brush, and a conveyor chain. White clams ( Mactra veneriformis ) cultured in mudflats were used as the research objects in this paper, and the mechanics and motion states of the shellfish on the vibrating screen were analyzed. The shellfish harvesting simulation response surface experiments based on the discrete element method (DEM) were conducted to analyze the influence of the main operating parameters on the quantity of shellfish harvested. Results The results revealed that the number of shellfish harvested was significantly influenced ( p < 0.01) by vibrating screen amplitude, first-stage spiral rolling stainless steel brush rotation rate, and harvester travel speed. The optimal combination of key parameters was 1.4 mm, 40 rpm, and 10 m/min, respectively. With these values, the projected shellfish crushing rate was 2.82% and the shellfish harvesting efficiency was 125 pieces/m 2 . The equipment was then manufactured and the shellfish harvesting verification test was performed under the same operating parameters as the simulation. Test results indicated that the harvesting efficiency of the equipment was 114 pieces/m 2 and the shellfish crushing rate was 6.97%. Discussion The shellfish harvesting work could be completed by the equipment effectively and with low loss. The results of this study provide a theoretical reference for a novel mechanized method of harvesting mudflat-buried shellfish.

Seasonal source identification and formation processes of marine particulate water soluble organic nitrogen over an offshore island in the East China Sea - Mengke Tian; Hao Li; Guochen Wang; Mengxin Fu; Xiaofei Qin; Da Lu; Chengfeng Liu; Yucheng Zhu; Xingzhang Luo; Congrui Deng; Sabur F. Abdullaev; Kan Huang (Science of The Total Environment, 2023)

An analytical method for the thermo-mechanics coupling study of thin-walled spherical shell structure - Xingji Zhu; Kainian Jiang; Qingchen Liu; Lin Tang; Longjun Xu; Guochen Zhao; Changqing Gong (European Journal of Environmental and Civil Engineering, 2022)

Influence of saturated zone depth and vegetation on the performance of vertical flow-constructed wetland with continuous feeding - Guochen Liu; Zonglian She; Mengchun Gao; Jiacheng Liang; Chunji Jin; Liang Guo; Yangguo Zhao (Environmental Science and Pollution Research, 2018)

Zn2+ and mPTP Mediate Endoplasmic Reticulum Stress Inhibition-Induced Cardioprotection Against Myocardial Ischemia/Reperfusion Injury - Guochen Wang; Hongping Huang; Huan Zheng; Yonggui He; Yidong Zhang; Zhelong Xu; Liu Zhang; Jinkun Xi (Biological Trace Element Research, 2016)

Consecutive combined response spectrum - Longjun Xu; Guochen Zhao; Qingyang Liu; Yujian Xie; Lili Xie (Earthquake Engineering and Engineering Vibration, 2014)

Adventitious shoot regeneration of oriental lily (Lilium orientalis) and genetic stability evaluation based on ISSR marker variation - Xiaomei Liu; Guochen Yang (In Vitro Cellular & Developmental Biology - Plant, 2012)

Identification of SCAR markers linked to or, a gene inducing beta-carotene accumulation in Chinese cabbage - Fenglan Zhang; Guochen Wang; Mei Wang; Xiucun Liu; Xiuyun Zhao; Yangjun Yu; Deshuang Zhang; Shuancang Yu (Euphytica, 2008)